2000
DOI: 10.1002/1097-0282(2000)57:6<325::aid-bip10>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of Raman or fluorescence spectra of biomolecules using specifically annealed thick gold films

Abstract: Annealing of “thick” metal films deposited onto a smooth dielectric substrate leads to high‐order self‐organization of metal clusters on the film surface. This work presents the first experimental evidence that the “thick” gold film (TGF) may be specifically annealed to serve as a substrate for surface‐enhanced fluorescence or surface‐enhanced Raman scattering (SERS) spectroscopy of the same molecule. High‐resolved SERS spectra of mitoxantrone (mitox) were recorded on the TGF annealed at 340°C whereas no Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…2c (spectra 3 and 4). As reported previously, PGF-350 enhance Raman scattering of adsorbed mitox, while PGF-290 enhance mitox fluorescence, so we have associated this selectivity of secondary emission enhancement with different overlap of molecular electronic transitions and localized plasmon band under resonance excitation [12]. Spectrum 5 in Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…2c (spectra 3 and 4). As reported previously, PGF-350 enhance Raman scattering of adsorbed mitox, while PGF-290 enhance mitox fluorescence, so we have associated this selectivity of secondary emission enhancement with different overlap of molecular electronic transitions and localized plasmon band under resonance excitation [12]. Spectrum 5 in Fig.…”
Section: Resultssupporting
confidence: 58%
“…Plasmonic film in contrast to plasmonic crystal [9][10][11] means disordered nanotextured metal surface in which SPP and/or localized plasmons (LP) could be excited under resonance conditions. In spite of non-periodic structure, plasmonic films possess some unique properties such as electromagnetic field enhancement and the selectivity of the enhancement effect at the certain frequencies within plasmon band as it was shown previously [12].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been found that coatings with predictable morphological and optical characteristics can be obtained by controlling the parameters of the processes for producing these gold films (deposition time for the nanoparticles, their concentration, the number of polyelectrolyte sublayers) [9]. This makes it possible to select by technical means the most efficient substrate for enhancing the luminescence intensity of a given adsorbate, while maintaining maximal overlap of the absorption spectrum of the fluorophore with the plasmon band of the metal film at the excitation frequency [13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in order to study the fluorescence as a function of the distance between the molecule and the metal, different intermediate dielectric layers (spacers) are used (proteins, phospholipids, organic acids, amines, and their derivatives [8,9], deposited on the metal substrate by the Langmuir-Blodgett method; polymers (polymethylmethacrylate, polylysine [8]), quartz [9], making it possible to controllably vary the distance from the luminophore to the metal.…”
mentioning
confidence: 99%